Fasciola hepatica LINAEUS, 1758 (Trematoda fasciolidae) IN THE BOCAIUVA DO SUL E TUNAS DO PARANA COUNTIES, IN THE STATE OF PARANA, BRAZIL - QUEIROZ, Valter da Silva (Scientia Agraria, 2000)
In studies done about Fasciola hepatica in 42 properties in the urban communities of Bocaiúva do Sul and Tunas do Paraná, in state of Paraná, Brazil, during the period of November 1998 to February 1999, we observed the following: Through the Molusca - Pulmonata fauna survey done in those mentioned properties, of the Molusca - Pulmonata population identified, 22 (52%) of the properties showed Lymnaea columella 4 (9%) presented Physa marmorata. In an investigation fulfilled through the dissection of the found mollusks, no larva of Fasciola hepatica were found in any of them. Trough lees parasitological investigation for egg survey accomplished with ovine and cattle herds samples of searched properties, the infection by F. hepatica was found in 4 (10%) of the properties. From the total of the of the properties, 2 (17,7%) of the ovine flocks and 3 (8%) of the cattle herds were infected. In laboratorial investigations aiming to test the Lymnaea columella and Pulmonata marmorata mollusks susceptibility to infections by miracidium arising from the local properties, only the Lymnaea columella has developed in infection. Through the study of the epidemiological aspect of the fasciola in cattle located in the properties in the urban area of the municipality of Bocaiúva do Sul, L. columella and P. marmorata were found during the whole period between January, 1995 and November, 1996, except in April, 1996 when only P. marmorata was verified. The highest peak of population of the two species was found in May, 1996. Concerning to the presence of natural infection by F. hepatica larva, only L. columella was verified in March and April, 1995. In the searched period, in thee surveys fulfilled, examining the animals individually through the parasite egg investigation using lees parasitological inquiry, we have got the following infection tables by F. hepatica. March/95: 9,09%, August/96: 40%, and November/96: 40% In the studied area we observed that there is a Fasciola hepatica with the autochthonal shape and the intermediate landlord is the Lymnaea colunela which is widely spread in the area, representing a risk as zoonosis.